Utilization of Moringa oleifera Lam. extracts as natural antioxidant in goat (Capra hircus linnaeus) meat products - Al-zaidi, Mohammed Awad Kadhim (2022)
The present study was envisaged to evaluate the use of Moringa oleifera leaf extract as natural preservative in goat meat. Aqueous extract of Moringa oleiferia mature leaves (60 days) exhibited strong antioxidant activity as determined by radical-scavenging activity of 1,1-diphenyl 2 picrylhydrazyl (DPPH) as IC50 value 18.54 μg/mL, high total phenolic content (48.36 mg of gallic acid equivalent per g). Based on preliminary trial, five treatments were formulated for marination on goat meat as follows: Control (C, without the Moringa oleifera leaves extracts (MOLE) treatment); positive control (PC, treated with 0.1% butylated hydroxytoluene (BHT)); T0.1 (treated with 0.1% MOLE); T0.5 (treated with 0.5% MOLE) and T1.0 (with 1.0% MOLE). The control and the extracts were treated on the Longissimus dorsi (LD), Infraspinatus (IF), Biceps femoris (BF) and Semimembranous (SM). The samples were marinated under refrigeration in high-density polyethylene (HDPE) bags for 7 days and assessed for various quality attributes (pH, water holding capacity, moisture, colour profile, and radical scavenging activity) on 1, 3 and 7 days, with sensory and texture profile analysis were assessed day 3 in addition to the above parameters. During refrigeration storage, all marinated muscles exhibited increased thiobarbituric acid reactive substances (TBARS) value, lowered water holding capacity (WHC) and increasing moisture content on day 3 followed by marginal decrease in moisture content on day 7. Within muscles, TBARS value of the control was recorded highest followed by T0.1, T0.5 and T1.0. A significant (p<0.05) reduction in redness and increase in yellowness of goat meat upon marination was due to addition of MOLE than in control. MOLE extract when added to meat was found to retard lipid peroxidation. A marked deterioration on sensory attributes was recorded with the advancement of storage period; with control exhibited lowest flavour scores among treatments. Marination with MOLE had significant effect on the mean shear force value of LD muscle. The moisture content of all treatments of all 4 muscles under studies exhibited significantly (p<0.05) lower moisture content on 7th day of storage. The pH showed an increasing trend with the advancement of storage days. The results of sensory evaluation showed that all estimation levels are within the scale 8, which lies between moderate like and like very much. The antioxidant activity of MOLE was found to be comparable to BHT. Addition of MOLE did not affect any of the sensory attributes of marinated goat meat. The MOLE at a level of 1% was sufficient to protect goat meat against oxidative rancidity comparable to BHT added samples.